Waqf Stock in Securities Companies (Models, and Perspectives of Islamic Social Finance) - Nurfattah, Arizqiya; Bachtiar, Royyan (Journal of Islamic Economics and Philanthropy, 2023)
The magnitude of cash waqf potential in Indonesia, which reaches 180 trillion, has not been realized, as evidenced by the acquisition of cash waqf of only 1 trillion. Product innovations continue to be presented in order to attract the interest of the Muslim community in waqf, one of which is stock waqf which is present as an alternative to cash waqf derivative products with the main target of stock investors mediated by securities. This research is qualitative research with a descriptive qualitative approach with the type of research library, the findings of the research show that the implementation of waqf shares by wakif or investors is bridged by securities companies, which are then channeled to the waqf asset manager (nazir).Â  The legal basis for waqf in stock waqf refers to the law of cash waqf because stock waqf is actually a derivative of cash waqf.